A review of the nutrition and feeding management of farmed tilapia throughout the culture cycle - Wing‐Keong Ng; Nicholas Romano (Reviews in Aquaculture, 2013)
Tilapia is the second most farmed fish group worldwide and over the past decade has quadrupled in production, largely due to their many characteristics conducive to aquaculture conditions as well as to the high marketability and relatively stable market prices. To keep pace with this rapid expansion, tilapia aquaculture will rely increasingly on more sustainable practices, but this must not be at the expense of decreased productivity, increased cost or compromised product quality. Since feed constitutes the major operating cost of tilapia farming, understanding their nutritional requirements, factors that may influence these requirements and implementing the most appropriate feeding management strategy is essential for the continued sustainability and scalability of the global tilapia industry. This review addressed these concerns by providing an overview of published nutrient requirement data and offered practical recommendations to the nutrition and feeding management of farmed tilapia, from broodstock to finishing feeds. The first section of this review extensively discusses the dietary protein/amino acids, lipids/fatty acids, carbohydrates, vitamin and mineral requirements of tilapia. Alternatives to marine‐based ingredients, which are used increasingly in tilapia feeds, are also discussed. This is followed by discussing practical feed management aspects at the commercial farm level including feed formulations, feed types and feeding rates/frequency throughout the culture cycle. Recent research indicating significant differences in nutrient requirements and utilization efficiencies of improved tilapia strains versus non‐improved strains are highlighted. This review aims to provide a comprehensive overview of tilapia nutrition and thus contributes to the continued global expansion of tilapia farming and the demand for their products.